Tissue Clock Beyond Time Clock: Endovascular Thrombectomy for Patients With Large Vessel Occlusion Stroke Beyond 24 Hours - Ghada A. Mohamed; Raul G. Nogueira; Muhammed Amir Essibayi; Hassan Aboul-Nour; Mahmoud Mohammaden; Diogo C. Haussen; Aldo Mendez Ruiz; Bradley A. Gross; Okkes Kuybu; Mohamed M. Salem; Jan-Karl Burkhardt; Brian Jankowitz; et al. (Journal of Stroke, 2023)
Background and Purpose Randomized trials proved the benefits of mechanical thrombectomy (MT) for select patients with large vessel occlusion (LVO) within 24 hours of last-known-well (LKW). Recent data suggest that LVO patients may benefit from MT beyond 24 hours. This study reports the safety and outcomes of MT beyond 24 hours of LKW compared to standard medical therapy (SMT). Methods This is a retrospective analysis of LVO patients presented to 11 comprehensive stroke centers in the United States beyond 24 hours from LKW between January 2015 and December 2021. We assessed 90-day outcomes using the modified Rankin Scale (mRS). Results Of 334 patients presented with LVO beyond 24 hours, 64% received MT and 36% received SMT only. Patients who received MT were older (67±15 vs. 64±15 years, P=0.047) and had a higher baseline National Institutes of Health Stroke Scale (NIHSS; 16±7 vs.10±9, P<0.001). Successful recanalization (modified thrombolysis in cerebral infarction score 2b-3) was achieved in 83%, and 5.6% had symptomatic intracranial hemorrhage compared to 2.5% in the SMT group (P=0.19). MT was associated with mRS 0–2 at 90 days (adjusted odds ratio [aOR] 5.73, P=0.026), less mortality (34% vs. 63%, P<0.001), and better discharge NIHSS (P<0.001) compared to SMT in patients with baseline NIHSS ≥6. This treatment benefit remained after matching both groups. Age (aOR 0.94, P<0.001), baseline NIHSS (aOR 0.91, P=0.017), Alberta Stroke Program Early Computed Tomography (ASPECTS) score ≥8 (aOR 3.06, P=0.041), and collaterals scores (aOR 1.41, P=0.027) were associated with 90-day functional independence. Conclusion In patients with salvageable brain tissue, MT for LVO beyond 24 hours appears to improve outcomes compared to SMT, especially in patients with severe strokes. Patients’ age, ASPECTS, collaterals, and baseline NIHSS score should be considered before discounting MT merely based on LKW.